To study the effect of solvent, viscosity, and temperature on the mouth-dissolving film of Withania somnifera Linn - Daud, Anwar; Bonde, Minal; Sapkal, Nidhi; Gaikwad, Naresh (Asian Journal of Pharmaceutics (AJP), 2014)
An oral-dissolving drug delivery system offers a solution for those patients having difficulty in swallowing tablets/capsules, and so on. Withania somnifera has been used to promote health and longevity by augmenting defenses against disease, arresting the aging process, revitalizing the body in debilitated conditions, and thus creating a sense of well-being.Commercially, it is available either in powder or liquid dosage forms that do not offer patient compliance. In the present study, an attempt has been made to formulate W. somnifera into thin oral films. An attempt was also made to study factorslike the effect of the type of solvent used for casting of the film, effect of drying temperature, and viscosity of the solution on the mouth-dissolving film of W. somnifera Linn. The mouth-dissolving films were prepared by the solvent-casting method. Prepared films were evaluated for film-forming capacity, appearance of film, tack test, thickness, in vitro disintegration time,folding endurance, tensile strength, and percentage elongation. This study illustrated that selected process variables have an influence on the physicomechanical properties of the mouth-dissolving film of W. somnifera Linn. Water was found to be an excellent solvent for casting when hydroxypropylmethylcellulose was used as a film former. When mouth-dissolving film of W. somnifera Linn was dried at lower temperatures, it showed optimum physicomechanical performances. Viscosity of the solution plays an important role in physicomechanical properties of the film; as the viscosity of solution increases, there is an increase in folding endurance, tensile strength, and percentage elongation.